2017
DOI: 10.1002/2017gl075392
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Upper Mantle Heterogeneity in Generating the Indian Ocean Geoid Low

Abstract: One of the most pronounced geoid lows on Earth lies in the Indian Ocean just south of the Indian peninsula. Several theories have been proposed to explain this geoid low, most of which invoke past subduction. Some recent studies have also argued that high‐velocity anomalies in the lower mantle coupled with low‐velocity anomalies in the upper mantle are responsible for these negative geoid anomalies. However, there is no general consensus regarding the source of this particular anomaly. We investigate the sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
7
29
0
Order By: Relevance
“…Each temporal gravity model has different characteristics and may help to retrieve different information depending on its data content and the application area it is used for. For instance, monthly models are very useful and important in monitoring the variations in the terrestrial hydrological cycle (Schmidt et al, 2006), ice melting (Velicogna, 2009), sea level change (Cazenave et al, 2009) and help to investigate climate-change-related variations in the Earth's system (Wahr et al, 2004), whereas daily solutions have the potential to be used to monitor short-term scale variations such as flood events and they contribute to assessing natural hazards as proven with the successful outcomes of the EGSIEM project (Gouweleeuw et al, 2018). The results are generally presented in terms of equivalent water height (EWH) or water column (Wahr et al, 1998;Wahr, 2007).…”
Section: Temporal Global Gravity Field Models Of the Earthmentioning
confidence: 99%
“…Each temporal gravity model has different characteristics and may help to retrieve different information depending on its data content and the application area it is used for. For instance, monthly models are very useful and important in monitoring the variations in the terrestrial hydrological cycle (Schmidt et al, 2006), ice melting (Velicogna, 2009), sea level change (Cazenave et al, 2009) and help to investigate climate-change-related variations in the Earth's system (Wahr et al, 2004), whereas daily solutions have the potential to be used to monitor short-term scale variations such as flood events and they contribute to assessing natural hazards as proven with the successful outcomes of the EGSIEM project (Gouweleeuw et al, 2018). The results are generally presented in terms of equivalent water height (EWH) or water column (Wahr et al, 1998;Wahr, 2007).…”
Section: Temporal Global Gravity Field Models Of the Earthmentioning
confidence: 99%
“…for top 100 km this is 30 × 10 21 Pa-s. T 0 and T are non-dimensional reference and actual temperatures obtained by using a thermal expansivity of 3 × 10 −5 K −1 that converts density anomalies into temperature anomalies (cf. Ghosh et al (2017) to the entire mantle (instead of only above 300 km depth) yields nearly identical results. To apply the temperature-dependent viscosity, we have non-dimensionalised temperature with respect to 1300 o C mantle potential temperature.…”
Section: Mantle Viscosity Structurementioning
confidence: 71%
“…A scaling (dlnρ/dlnV s ) of 0.25 is used to convert seismic velocity anomaly to density anomaly (cf. Ghosh et al (2017)).…”
Section: Mantle Flowmentioning
confidence: 99%
“…Thus, we utilized the 3‐D velocity model constructed using both the P and S wave velocities, extracted from the appropriate global tomography model, to migrate the PRFs to depth (3‐D migration). The model GyPSuM (Simmons et al., 2010) is considered for this purpose, since this is one of the models that best explains the IOGL (Ghosh et al., 2017). Further, we also used the LLNL‐G3D‐JPS (Simmons et al., 2015) and MEAN2 models to compare the results.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, based on the simulation of density‐driven mantle convection using different global tomography models, Ghosh et al. (2017), concluded that low‐density anomalies in the depth range of ∼300 to 900 km are only responsible for the IOGL.…”
Section: Introductionmentioning
confidence: 99%